The effect of Cinnamtannin B1 on cell proliferation and glucose uptake of 3T3-L1 cells - Bakhtiar, M. Taher; Abdul Majid, Fadzilah Adibah; Sarmidi, Mohamad Roji (Natural Product, Inc., 2007)
The effects of cinnamtannin B1 on cell proliferation and glucose uptake of 3T3-L1 cells were examined. Cinnamtannin B1 promoted cell proliferation of 3T3-L1 adipocytes at a concentration range between 0.11-0.17 mM. The effect of cinnamtannin B1 on cellular 2-deoxy-D-[1-3H] glucose uptake in differentiated 3T3-L1 adipocytes, following treatment with a 0.11 mM concentration of cinnamtannin B1 for 15, 30 and 60 minutes, was an increase in the glucose uptake from a basal value to 702.0,1111.0 and 2226.0 cpm, respectively (p<0.005). The comparable glucose uptakes with insulin treatment were 660.0, 1039.0 and 2135.0 cpm, respectively. Wortmannin and cytochalasin B were found to inhibit cinnamtannin B1-stimulated glucose uptake, but sodium orthovanadate increased the glucose uptake.